PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SITIUNG KABUPATEN DHARMASRAYA - Martin, Ellusi; Rahmi, Rahmi; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
Background of this research is resulf of studentâs mathematic comprehension on SMPN 1 Sitiung grade VIII are still low it can be seen on their result in first semester in 2012/2013. One solution to improve studentâs mathematic comprehension by applying active learning strategy on Instant Assessment type. This research has a purpose to know whether students mathematic comprehension by applying active learning strategy on Instant Assessment type is better than studentâs mathematic comprehension by applying convensional learning on SMPN 1 Sitiung at VIII grade. The research method is experimental research. The population is studenâs in SMPN 1 Sitiung at grade VIII in 2012/2013 it consists of seven classes. Experimental class is VIII.D and control class is VIII.E the instrument of this research is test of studentâs mathematic comprehension. Test type of this research is essay form the realibility of the testÂ Â Â 0,87. Based on the data analysis the researcher found the mean score of students math comprehension in experimental class 75,64 meanwhile in control class is only 53. Â It means that the mean score in experimenthal class is higher that control class The analysis of data is done by software MINITAB the researcher got p-value=0,00 it is smaller than . Therefore the researcher conclasdes that students mathematic comprehension by applying actif learning on Instant Assessment type is better than studentâs mathematic comprehension by applying convensional learning it can be proven on 95%.